Prospective risk for suicidal thoughts and behaviour in adolescents with onset, maintenance or cessation of direct self-injurious behaviour - Koenig, Julian; Brunner, Romuald; Fischer-Waldschmidt, Gloria; Parzer, Peter; Resch, Franz; Kaess, Michael (European child & adolescent psychiatry, 2017)
Direct self-injurious behaviour (D-SIB) is associated with suicidal behaviour and suicide risk. It is not known if D-SIB cessation reduces these risks. The aim of this study was to explore trajectories of D-SIB and their prospective influence on suicidal thoughts and behaviour during adolescence. Data (n = 506; 62.06 % females, 14.53 years) from the Saving and Empowering Young Lives in Europe study were analysed. D-SIB and suicidal thoughts and behaviour were assessed at baseline (T0), 1- (T1) and 2-year follow-up (T2). Onset and maintenance of D-SIB between T0 and T1 were associated with a two to threefold increased odds ratio for suicidal thoughts and behaviour at T2. Suicidal thoughts and behaviour in those terminating D-SIB before T1 were similar compared to those with no life-time history of D-SIB. Late onset and maintenance of D-SIB prospectively indicate risk for suicidal thoughts and behaviour. This is the first study showing that D-SIB cessation reduces later risk for suicidal thoughts and behaviour in adolescence. Suicide prevention efforts should set one focus on reducing adolescent D-SIB.
First online: 24 August 2016
Gesehen am 29.10.2018